Penerapan Standar Operasional Prosedur (SOP) Dalam Pengurusan E-KTP Untuk Mewujudkan Good Governance Di Kantor Camat Medan Amplas Kota Medan - Anisah Putri Nabilah; Robinson Sembiring (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
The purpose of the study was to find out the portrait of the SOP on the management of E-KTP from the aspects of transparency, accountability, and the rule of law at the Medan Amplas Sub-District Office, Medan City. This study uses descriptive qualitative research methods with primary and secondary data collection techniques. The results showed that the SOP for the management of E-KTP at the Medan Amplas sub-district office was not optimal in providing services to the community. This is evidenced by the complaints from the publik regarding the procedure and time for completing the E-KTP and the unsatisfactory attitude of the employees.